2020
DOI: 10.3390/foods9101478
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Extraction of Bioactive Principles from Blackcurrant Leaves and Chrysanthellum americanum: A Comparative Study

Abstract: The water-based extraction of bioactive components from flavonoid-rich medicinal plants is a key step that should be better investigated. This is especially true when dealing with easy-to-use home-made conditions of extractions, which are known to be a bottleneck in the course for a better control and optimization of the daily uptake of active components from medicinal plants. In this work, the water-based extraction of Blackcurrant (Ribes nigrum) leaves (BC) and Chrysanthellum americanum (CA), known to have c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Several studies have shown that the medicinal plants that make up this recipe follow these trends. Cao-Ngoc et al, showed that the aqueous extract of Chrysanthelllum americanum DC was mainly composed of flavonoids (flavanones, flavones and aurones) and phenolic acids (hydroxycinnamic acid) [22]. In a study conducted in Burkina Faso, Guenne et al, evaluated the antioxidant capacity and antilipoxygenase potential of Chrysanthelllum americanum DC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the medicinal plants that make up this recipe follow these trends. Cao-Ngoc et al, showed that the aqueous extract of Chrysanthelllum americanum DC was mainly composed of flavonoids (flavanones, flavones and aurones) and phenolic acids (hydroxycinnamic acid) [22]. In a study conducted in Burkina Faso, Guenne et al, evaluated the antioxidant capacity and antilipoxygenase potential of Chrysanthelllum americanum DC.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of P. cuspidatum extracts and four analytical standards (polydatin, emodin, resveratrol and chlorogenic acid) were evaluated towards hyaluronidase catalytic activity using an offline CE-based assay optimized in a previous study [ 97 ]. CE assays were carried out with some adjustment considering the presence of EtOH in plant extracts as well as in standards and its concentration was limited to 5% of the final volume.…”
Section: Methodsmentioning
confidence: 99%
“…According to the report of Cao-Ngoc with some modifications, the raw materials (15.0 g) were moistened with 180 mL of 95% ethanol and swelled in a closed container for 3 h. Then, the swollen material was transferred into the percolator, and the appropriate amount of 95% ethanol was added to extract for 24 h. After that, the first concentrated extract was collected. Extraction was continued until the constituents were completely exhausted.…”
Section: Materials and Methodsmentioning
confidence: 99%